Neurological Transitions. - Getzell, Jefrey H. (Optometry & Visual Performance, 2016)
Neurological transitions occur when the patient's style of vision does not match the changes they are making through vision therapy/training programs. As patients realign vision coordinates with postural coordinates in VT, the stage is set for a transition. In the realignment of vision with postural coordinates, unresolved emotional conflicts may come to consciousness. This was first described in the literature by Larry MacDonald, OD. During transitions, patients undergo three passages, which often involve physical, physiological, and cognitive/emotional changes. The changes common to transitions include headaches, brain fog, fatigue, and body tension. Bruce Wolf, OD, a pioneer behavioral optometrist, created visual training procedures that intentionally provided the patient opportunities to develop a matching or re-alignment of the visual and kinesthetic through the use of dissociating or doubling glasses. The personal experience of children and adults going through a transition is described.